Color of human eye. Morphologic correlates and conditions that affect iridial pigmentation - Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Iris color is still considered as relevant and not exactly understandable clinical problem. This problem seems to be especially important if we considered that iris color can changed with age, some general and local disorders and application of different medications. This publication draw attention to past and contemporary opinions of morphologic correlations and some conditions that affect iris color.